Trends of Hematopoietic stem cell transplantation in the Eastern Mediterranean region, 1984–2007 - Ahmed, S.O. (2011)
Hematopoietic stem cell transplantation (HSCT) activity was surveyed in the 9 countries in the WHO Eastern Mediterranean (EM) region that are reported to carry out transplants. Between the years of 1984 and 2007, 7933 transplants were reported. The total number of HSCT per year has continued to increase, with a plateau in allogeneic HSCT (allo-HSCT) between 2005 and 2007. Overall, a greater proportion of transplants were allogeneic HSCT (allo-HSCT) (n=5761, 77%) compared to autologous HSCT (ASCT) (n=2172, 23% ASCT). Of 5761 allo-HSCT, acute leukemia constituted the main indication (n=2124, 37%). There was a relatively high proportion of allo-HSCT for bone marrow failure (n=1001, 17%) and hemoglobinopathies (n=885, 15%). The rate of unrelated donor transplants remained low, with only 2 non-umbilical cord matched unrelated donor (MUD) allo-HSCT reported. One hundred umbilical cord (UCB) transplants were reported (0.017% of allo- HSCT). Peripheral blood stem cells (PBSC) were the main source of graft in allo-HSCT, and PBSCT increasingly constitutes the main source of stem cells. Reduced intensity conditioning was utilized in 5.7% of allografts over the surveyed period. ASCT numbers continue to increase. There has been a shift in the indication for ASCT from acute leukemia to lymphoproliferative disorders (45%) followed by myeloma (26%). The survey reflects transplantation activity according to the unique health settings of this region. Notable differences in transplant practices as reported to the European Group for Blood and Marrow Transplantation (EBMT) over recent years are addressed.